South Africa's proposed new Marine Protected Area around the Prince Edward Islands: An analysis of legal obligations, options and opportunities - Nel, Deon (Institute of Marine and Environmental Law, 2014)
This dissertation examines the international, regional and national legal context for the declaration of a large multi-zoned MPA around the Prince Edward Islands. In particular I examine South Africa's obligations in terms of international and regional treaty law as well as its commitments to global policy statements. Legal options and opportunities for providing the most comprehensive, and yet practical, legal protection for such a MPA are examined. Recommendations are made based on this analysis.